2023
DOI: 10.12688/f1000research.131599.1
|View full text |Cite
|
Sign up to set email alerts
|

“Am I Masculine?” A metasynthesis of qualitative studies on traditional masculinity on infertility

Abstract: Background: The rate of infertility is increasing day by day. According to studies conducted worldwide, 30 million men are diagnosed with infertility. Cases of infertility are often associated with a failure to become male in society. Procreation and gender roles are often closely linked so that infertile men are often considered the second sex. Sometimes, this condition makes men question their masculinity. Methods: We performed a systematic review and metasynthesis with the Preferred Reporting Items for Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…While this was not the intention of this review, the metatheme "Crippling social pressure" was voiced by men across all included studies, which is interesting as none of the articles' primary aim was to explore masculinity. Although this is not the first time the notion of masculinity in male infertility has been discussed in the literature (Bell, 2016;Pakpahan et al, 2023;Throsby & Gill, 2004), it is among the first to capture men's experiences in relation to infertility, of which the power of masculine norms and societal expectations was prominent. Thus, there is now an understanding that males feel oppressed by their masculine status and "feel less of a man" (Arya & Dibb, 2016, p. 244) when living with infertility.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While this was not the intention of this review, the metatheme "Crippling social pressure" was voiced by men across all included studies, which is interesting as none of the articles' primary aim was to explore masculinity. Although this is not the first time the notion of masculinity in male infertility has been discussed in the literature (Bell, 2016;Pakpahan et al, 2023;Throsby & Gill, 2004), it is among the first to capture men's experiences in relation to infertility, of which the power of masculine norms and societal expectations was prominent. Thus, there is now an understanding that males feel oppressed by their masculine status and "feel less of a man" (Arya & Dibb, 2016, p. 244) when living with infertility.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, there has been a more thoughtful inclusion of men into reproductive research (Hinton & Miller, 2013), which challenges the norm that men are unable to identify their emotions (Fischer & Good, 1997) and do not want to talk (Arya & Dibb, 2016). Consequently, such methods have created the emotional space men very much need, but lack (Seidler, 2007), likely due to the social expectations and masculine norms embedded within society (Pakpahan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is not surprising that infertility and its diagnosis can have a different impact on men and women. Sex and gender influence the diagnosis, course, treatment, and outcomes of many illnesses, as well as the access to and acceptability of psychosocial and health care [27,28]. To measure any of these aspects, both concepts-sex and gender-must be clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations providing reproductive health services found that cultural norms often pressure infertile men socially and psychologically (Pakpahan et al., 2023). For instance, in some traditional societies, such as Iran, women are expected to bear children, while men are responsible for carrying on the family line.…”
Section: Introductionmentioning
confidence: 99%